2020
DOI: 10.1080/09668136.2020.1736988
|View full text |Cite
|
Sign up to set email alerts
|

‘You Don’t Need Santa Monica!’ The Objectification of Elderly Care Receivers in Russia

Abstract: The article presents the case of non-governmental elderly care provision in St Petersburg, Russia. In an attempt to fill the gap in existing care research, it discusses the objectification of care receivers and the inequalities between caregivers and care receivers in the case of caregiving under circumstances of non-governmental sector professionalisation. The empirical part of the article is based on fieldwork carried out in 2014-2015 in St Petersburg, consisting of 48 interviews, numerous observations and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…The same dilemmas are reflected at the regional level, with documents and specific active ageing programmes navigating between the proclaimed intent to change perceptions of ageing in general and the specific limitations, boundaries and perceived needs of their target group. According to our earlier research projects in northwest Russia (Holavins 2020b) and analysis of regional-level documents in Moscow and Saratov, 10 regional programmes are largely in line with the federal-level policy documents regarding active ageing. Government, third sector and private organisations that provide social services are generally supportive of active ageing.…”
Section: Regional-level Discourses Of Active Ageingmentioning
confidence: 72%
See 3 more Smart Citations
“…The same dilemmas are reflected at the regional level, with documents and specific active ageing programmes navigating between the proclaimed intent to change perceptions of ageing in general and the specific limitations, boundaries and perceived needs of their target group. According to our earlier research projects in northwest Russia (Holavins 2020b) and analysis of regional-level documents in Moscow and Saratov, 10 regional programmes are largely in line with the federal-level policy documents regarding active ageing. Government, third sector and private organisations that provide social services are generally supportive of active ageing.…”
Section: Regional-level Discourses Of Active Ageingmentioning
confidence: 72%
“…Previous studies have shown that this empowerment paradox-the contradiction between the inclusive rhetoric of active ageing and paternalistically objectifying neoliberal policy implementation-exists in Russia (Sinyavskaya 2015;Holavins 2020c). However, so far, little has been said on how active ageing is seen by older people themselves and how they construct ideas about ageing (Boudiny 2013;Mendes 2013).…”
Section: Active Ageing: Background and Critiquementioning
confidence: 99%
See 2 more Smart Citations
“…Опираясь на концепцию заботы, историческую социологию и политэкономический анализ, М. Файн и Б. Дэвидсон раскрывают противоречия в уходе за престарелыми в условиях маркетизации социальной заботы в Австралии [Fine, Davidson, 2018]. Исследования формальной и неформальной заботы показывают, как с переходом на проектную деятельность меняются форматы отношений: неолиберальные ценности и инструменты превращают отношения в духе Gemeinschaft, характерные для низовых организаций самопомощи, в рационализированные стили руководства и увеличивают разрыв между менеджерами и работниками, специалистами и клиентами, поощряют иерархию и снижают уровень участия исполнителей и получателей услуг в принятии решений [Holavin, 2020]. А благодаря методологической оптике гендерных исследований с учетом концепции разнообразия удается не только обнажить возрастающее давление неолиберального порядка на семейные ресурсы [Критическая социология заботы…, 2019], но и выстроить программу интерсекционального подхода в изучении новых социальных отношений [Choo, Ferree, 2010].…”
Section: Introductionunclassified